Stabilization and Problematization. The Names in Victoriano Salado Alvarez’ Literary Texts - Vital Díaz, Alberto (Anales de Literatura Hispanoamericana, 2021)
The present paper aims to show the use of anthroponyms in the narrative work of Mexican writer Victoriano Salado Álvarez (1867-1931). The analysis goes through four different types of texts, highly representatives of Victoriano Salado’s work: 1) short stories with innovative tendencies from a stylistic or discursive standpoint; 2) short stories of conventional plot; 3) dialogues or theatrical-like texts, and 4) fragments of historical novel, mainly from his work Episodios nacionales mexicanos (1902-1906). These usages are shown in the line of the onomastic influence by a Hispanic tradition with clear traces of Miguel de Cervantes and Benito Pérez Galdós. This paper claims that usage of proper names is closely related not only to a discursive strategy but also to a poetics of literature through which we may see a useful field of inquiry of literary texts. In an author such close to realism of Spanish tradition as Salado Álvarez, formal principles like stability of names as well as the identity “name-character”, through which here we call the Golden rule of name, are set into contrast with other principles like destabilization, instability and problematization in the literary onomastics, closer to subsequent avant-garde traditions in literature.